USE OF IDIOMS IN ENGLISH AND UZBEK LANGUAGES - Rakhmonalieva Gullolakhon Abduvokhid qizi (American Journals Publishing, 2023)
This article provides a general understanding of phraseology and phraseological units, which is an important branch of linguistics, as well as examples of linguists who have conducted research in this field. The use of phraseological units and idioms in English and Uzbek languages is illustrated with examples.
Keywords: Phraseology, phraseologism, phraseological units, idiom, sentence idioms, semi-sentence idioms.